Correlates Of Anaemia and Worm Infestation Among Rural Pregnant Women: A Cross Sectional Study from Bengal - Sinjita Dutta; Sita Chatterjee; Debasish Sinha; Bobby Pal; Mausumi Basu; Aparajita Dasgupta (Medsci Publications, 2013)
Background: Anemia is the commonest nutritional problem among pregnant women. It is more common in developing countries because of varied socio-cultural problems. Objectives: To find out the prevalence of worm infestation and anaemia among pregnant women along with their socio-demographic characteristics, dietary habits and state of personal hygiene and elicit the association, if any, with anemia and worm infestation Materials and methods: A cross-sectional study was carried out among pregnant mothers attending the antenatal clinic at Nasibpur Union Health Center. All antenatal mothers who came for antenatal checkup for the first time to the health centre on two prefixed days of the week during the study period were interviewed. The reports of their stool and haemoglobin examination were followed up. Results: 82% of the pregnant women were suffering from anemia.25% of the study population had worm infestation. Age at marriage, green leafy vegetable, fruit and flesh food intake of at least 4 days a week, use of lemon with food most of the time, avoiding the practice of eating last in the family, handwashing with soap and water before eating and use of footwear outside the house were statically significant with hemoglobin concentration. Only religion and handwashing practice with soap and water before eating had statistically significant association with worm infestation. Conclusion: The study showed that certain protective factors like diet and personal hygiene if addressed at the time of antenatal checkup can reduce the number of cases of anemia significantly.